2019
DOI: 10.32604/jrm.2019.04881
|View full text |Cite
|
Sign up to set email alerts
|

Leaves Based Lubricant Additive Towards Improving Tribological Properties

Abstract: Three kinds of crop leaf-surface waxes were extracted from wheat, corn and broomcorn leaves, respectively. The crop leaf-surface waxes as lubricant additives were added to synthetic ester and the friction and wear properties of prepared lubricants for steel-aluminum and steel-copper friction pair were investigated in detail. The scanning electron microscopy (SEM) and secondary ion mass spectrometry (SIMS) were employed to explore the friction mechanisms. The results show that crop leaf-surface waxes could succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Meanwhile, with the frequency ranging from 2 to 5 Hz, all the lubricants exhibited a slow increase in COFs and wear widths. It also can be found that BS mucilage exhibited the biggest reduction in COFs and wear widths, which indicated that BS mucilage could generate a high-performance lubricating film on the friction surface at various frequencies [28]. Therefore, BS mucilage possessed a superior friction reduction and anti-wear abilities for steel/steel contact pair under various frequencies.…”
Section: Tribological Properties Of Lubricants Under Steel-steel Friction Pairmentioning
confidence: 85%
See 4 more Smart Citations
“…Meanwhile, with the frequency ranging from 2 to 5 Hz, all the lubricants exhibited a slow increase in COFs and wear widths. It also can be found that BS mucilage exhibited the biggest reduction in COFs and wear widths, which indicated that BS mucilage could generate a high-performance lubricating film on the friction surface at various frequencies [28]. Therefore, BS mucilage possessed a superior friction reduction and anti-wear abilities for steel/steel contact pair under various frequencies.…”
Section: Tribological Properties Of Lubricants Under Steel-steel Friction Pairmentioning
confidence: 85%
“…Obviously, the COF and wear scar widths also slowly increased with the frequency ranging from 2 to 5 Hz. Among the additives, SE+BS mucilage still exhibited lower COFs and wear scar widths, indicating that BS mucilage could effectively separate the friction interface to exhibit a better friction reduction and anti-wear abilities than others for steel-aluminium friction pair at different frequencies [28].…”
Section: Tribological Properties Of Lubricants Under Steel-aluminium Friction Pairmentioning
confidence: 97%
See 3 more Smart Citations